APPLYING LISTEN, READ, DISCUSS (LRD) STRATEGY TO PORTRAY STUDENT’S READING COMPREHENSION - Wahyuni, Resty; Siregar, Alfitriani; Faradila, Adelia (Universitas Negeri Medan, 2023)
The purpose of this study is to know the portrayal of student's in mastering reading comprehension after taught by LRD strategy. To improve students ' reading skills, researchers used the Listen Reading Discuss (LRD) method as a teaching method to assist students in improving their reading skills. The type of Applied Research is class action research consisting of two cycles, each cycle consists of planning, action, observation and reflection. Based on the results of this study, there is an increase in reading ability. This can be seen from the average pre-test score of 56.28, post-test cycle I of 69.17, and post-test cycle II of 89.05. by increasing the percentage of mastery of classical learning by 20% in the pre-test, 60% in the first cycle and 97.14% in the second cycle. Learning English with the Listen Reading Discuss (LRD) method has succeeded in improving student skill achievement in Class X of SMA Brigjen Katamso II for the 2022/2023 academic year. Finally, the researcher suggested to the teachers to use the LRD method as a method of teaching and learning process in terms of reading skills.